Functional Response of Myopopone castanea (Hymenoptera: Formicidae) on Prey Oryctes rhinoceros (Coleoptera: Scarabaeidae) - Widihastuty, Maryani Cyccu Tobing, Marheni, Retna Astuti Kuswardani (International Journal of Advanced Science and Technology, 2020)
The use of ants as biological agents has been known for a long time. Ants Myopopone castanea is a predator for pre-adult pests of Oryctes rhinoceros which is one of the important pests in oil palm plants. Understanding the relationship between predators and prey is important in ecology. Functional response is one component in assessing interactions between predators and prey. Functional response provides a quantitative description of predatory behavior when meeting prey with different prey densities, therefore this study was conducted to determine the functional response of M. castanea ants to O. rhinoceros prey with various prey densities. The study was conducted by using 50 ants of M. castanea worker and 50 ant larvae which were inserted into a glass box that had been filled with soil and pieces of palm oil which had decayed about 1 cm thick. The density of prey used was 5, 8, 11 and 14 individuals 2nd instar larvae of O. rhinoceros.The results showed that predation by M. castanea ants increased with increasing prey density. Predation in the first hour of observation is the highest predation and then decreases in line with the length of the observation. Response functional of M. castanea ant to prey O. rhinoceros is type II of functional response. To improve the effectiveness of predatory predation, more comprehensive efforts are needed in implementation of biological control.